THE POLITICAL FUNCTIONS OF DEATH: extrajudicial executions in Colombia, 2002-2010 - Berrio, Hernando Londoño (Universidade de Brasília, 2018)
Abstract: This article analyses the extrajudicial executions that took place in Colombia during the 2002-2010 period under the government of ex-President Alvaro Uribe Velez, distinctive for their cruelty: first, they were justified as executions of the “enemies” of the state (guerillas, paramilitaries, drug traffickers, etc.), “killed in combat” in defensive operations of the Colombian Armed Forces, when in fact they were defenseless victims arbitrarily assassinated in simulated confrontations; second, the thousands of such cases were a consequence of a policy that evaluated military personnel in terms of “enemy body count”, establishing remunerations, prices and recognition  accordingly. This institutional violence was at the service of wretched objectives of political power, which used the body count statistics as proof of the success of its “punitive populism” in order to ensure the re-election of then President Uribe; it concealed the shortcomings of the government negotiations with the paramilitaries as well as the cohabitation of the state with these actors; it bolstered the feeling of “citizen safety” through the criminalization of poverty. Finally, it utilized a number of strategies to ensure that these crimes would go unpunished by trying them in military courts and later by attempting to introduce the privileges of the military jurisdiction into the legal framework of the Special Jurisdiction for Peace.